Analisis Sistem Akuntansi Persediaan Barang Dagang Pada UMKM MiMa Frozen Food - Pratama, Sintya Musi; Jefri, Riny (JURNAL PUNDI, 2024)
In its application, the inventory accounting system often faces problems with inaccurate recording data, such as differences between the recorded amount of inventory and the number of physical goods, which can cause financial and operational losses. The purpose of this research is to determine the recording of merchandise inventory at UMKM MiMa Frozen Food as well as inventory problems regarding the factors that cause differences between the recorded inventory amount and the number of physical goods. This research uses a qualitative descriptive method with observation, interviews and documentation. The results of this research show that inventory recording uses a perpetual recording system using the "Qasir" application system. The inventory valuation method applied is appropriate, namely by choosing the FIFO method where goods that come in first will be released first so as to avoid expiration problems. Meanwhile, several causes of inventory discrepancies are human error (data input and calculations), system errors, different goods from distributors, and damaged or expired goods that are not recorded.